Numerical and analytical model for serviceability limit states of RC elements - Docevska, M., Arangjelovski, T., Markovski, G., Nakov, D. (Croatian Association of Civil Engineers, 2018)
A numerical and analytical model for prediction of serviceability limit states of flexural reinforced concrete members is outlined. The considered beam elements are investigated under short-term and long-term bending load. The numerical and analytical model is validated using existing experimental data. Both analyses provide reliable estimation of in-service deflections. A multi-directional fixed crack model is included in the numerical model to account for the non-linear post-cracking behaviour of concrete. For long-term analysis, time-dependent effects of concrete, creep and shrinkage are employed in both models through viscoelastic concrete behaviour.
Keywords: creep and shrinkage, long-term deflections, moment-curvature, crack pattern, tension-stiffening